Sunrise Model “Transcultural Nursing Leininger” on Toddler Stunting Incidents - Putri, Raden Roro Dewi Rahmawaty Aktyani; Romadhon, Wimar Anugrah (Journal of Ners and Midwifery, 2024)
Stunting is chronic malnutrition due to prolonged lack of nutrients, short or very short stature based on length/height for age. It is estimated that nearly a quarter of children in Indonesia are stunted. Stunting is an unresolved nutritional problem in Indonesia. The purpose of this study was to analyze the factors of stunting in toddlers based on the Transcultural Nursing theory. The research was conducted in the working area of Puskesmas Panggungrejo, Margomulyo Village. The sampling technique used purposive sampling. The sample size of this study was 154 respondents. The dependent variable of this study is the incidence of stunting. Independent variables consisted of technological factors, religiosity and philosophy, social support, cultural values and lifestyles, politics and legal, economic and educational factors. Data were collected using a questionnaire and analyzed using the Spearman rank statistical test with a significance level of α <0.05. The results of this study indicate that there is a relationship between technological factors p = 0.000, religiosity and philosophy factors p = 0.010, social support factors p = 0.002, cultural values and lifestyle factors p = 0.000, political and legal factors p = 0.000, economic factors p = 0.021 with the incidence of stunting while the education factor p = 0.128 is not associated with the incidence of stunting.